Importance of Clothing Brands in the Lives of Children - Challenge for Teachers - Lovšin, Francka; Brina, Lorger; Koch, Verena (Pedagogika, 2014)
This paper aims to determine how clothing brands affect children’s peer relations. The study was carried out by surveying 145 students. The results indicate that children are familiar with different clothing brands but they prefer sports brands. Brands were not the most important decision factor in purchasing process. The brands like decision factor were more important for older children and boys. Older children are also more often associated possession of (non) appropriate clothing brands with negative responses from other children. The children who were afraid of ridiculing of another children also felt more self-confident wearing popular brands of clothing.